Respuesta :

Hello there!

Let me try this one out!

[tex]6 ^{x-6} = \frac{1}{1296} [/tex]

We can start by taking log of both sides

[tex]log(6 ^{x-6}) = log( \frac{1}{1296})[/tex]

[tex](x - 6)(log(6)) = log( \frac{1}{1296})[/tex]

Since we are solving for x:

[tex]x - 6 = \frac{log(1/1296)}{log(6)} [/tex]

I used a calculator to help me solve the right part :)

x - 6 = - 4

Now we can add 6 on both sides

x - 6 + 6 = - 4 + 6

x = 2

I hope this helps! Let me know if you have any questions about the answer.